STANDARDISATION AND QUALITY EVALUATION OF SPREADS USING FRUIT EXTRACTS AND TENDER COCONUT PULP - E, Shahanas; Panjikkaran, Seeja Thomachan; E. R., Aneena; C.L., Sharon (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2015)
Spreads were prepared using extracts of guava, Jack fruit rind and plantain with tender coconut pulp. Organoleptic evaluation was conducted using score card. Textural quality parameters were analysed using a texture analyser. Physico - chemical qualities of blended spread were estimated initially and at monthly intervals for a period of six months. Spread was evaluated for Bacteria, Yeast and Mould initially and at the end of storage. Cost of production was calculated.